2017
DOI: 10.3892/etm.2017.5114
|View full text |Cite
|
Sign up to set email alerts
|

Uterine artery blood flow and microvessel density by vaginal color Doppler ultrasonography in embryo implantation failure

Abstract: The purpose of this study was to investigate the clinical application of uterine artery blood flow parameters by vaginal color Doppler ultrasonography in patients with repeated embryo implantation failure and to examine the correlation between uterine artery blood flow parameters and microvessel density (MVD). We monitored the outcomes of in vitro fertilization and embryo transfer in eighty patients. We divided the patients into two groups: Pregnancy (successful pregnancy, n=50) and repeated implantation failu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(15 reference statements)
0
6
1
Order By: Relevance
“…Accordingly, we conducted uterine arterial blood flow measuring on women undergoing IVF and noted that the UAI of some RIF patients was relatively elevated. Notably, previous studies have found that the uterine artery PI and subendometrial blood flow RI were higher in RIF patients than controls, meanwhile the waveform pattern of uterine artery altered in patients reporting RIF 23 . However, in the current study, the recruited women who conceived in the control group may show some minor differences in UAI compared with fertile women due to the application of hormones and other drugs during IVF treatment.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Accordingly, we conducted uterine arterial blood flow measuring on women undergoing IVF and noted that the UAI of some RIF patients was relatively elevated. Notably, previous studies have found that the uterine artery PI and subendometrial blood flow RI were higher in RIF patients than controls, meanwhile the waveform pattern of uterine artery altered in patients reporting RIF 23 . However, in the current study, the recruited women who conceived in the control group may show some minor differences in UAI compared with fertile women due to the application of hormones and other drugs during IVF treatment.…”
Section: Discussioncontrasting
confidence: 53%
“…Notably, previous studies have found that the uterine artery PI and subendometrial blood flow RI were higher in RIF patients than controls, meanwhile the waveform pattern of uterine artery altered in patients reporting RIF. 23 However, in the current study, the recruited women who conceived in the control group may show some minor differences in UAI compared with fertile women due to the application of hor- PRL mRNA levels in peri-implantation endometrial tissues, suggesting impaired decidualization in RIF patients. Insufficient endometrial angiogenesis is associated with increased resistance to endometrial blood flow from uterine artery.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…3 RIF is a form of refractory infertility with unknown aetiology, and it is defined as a failure to achieve a clinical pregnancy after transfer of four or more goodquality embryos in a minimum of two IVF cycles in a woman under the age of 40. 4 The failure of implantation may be a consequence of embryo factors (genetics, sperm contribution, and immunologic factors) or uterine factors (uterine anatomy, endometrium, and thrombophilia), whereas the causes of RIF are still poorly known. 5 It has been suggested that the abnormal maternal expression of genes associated with angiogenesis, immunity and apoptosis interferes with successful implantation.…”
Section: Introductionmentioning
confidence: 99%
“…It's necessary to understand that in the case of chronic endometritis ultrasonic diagnostics allows to reveal the inflammatory process so much as its consequences, which are shown as structural and anatomical modifications of uterus. During ultrasonic diagnostics it's absolutely important to determine risk factors, as we can observe different ultrasound features in each specific situation (5,6).…”
Section: Introductionmentioning
confidence: 99%